KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA SEBELUM DAN SAAT PANDEMI COVID-19 - Jenice Corputty; Daniel Yohannis Titapasanea; Junus Paulus Patty (Jurnal Administrasi Terapan, 2025)
This research aims to determine differences in the financial performance of manufacturing companies listed on the Indonesia Stock Exchange before and during the Covid-19 pandemic. The population in this study is manufacturing companies in the Consumer Goods Industry sector. The sample determination used the purposive sampling method and for the sample size using the slovin formula so that 18 companies were obtained. The data used is the annual financial report for the 2018-2021 period. The data analysis techniques used in this study are the Paired Sample T-Test. Hypothesis testing was determined based on the results of the normality test with a significance level of 5% (0.05). The results of this study show that in the statistical analysis of descriptive financial performance before Covid-19 in 2018-2019 has a minimum value of 9.49, a maximum value of 13.14, a mean value of 11.4838, and a standard deviation of 0.98136. Meanwhile, financial performance during the Covid-19 pandemic had a minimum value of 8.46, a maximum value of 12.93, an average value (mean) of 11.0488, and a standard deviation of 1.19108. The results of the normality test showed a significance value of 0.200, the value was greater than 0.05 so that the data was declared to be normally distributed. And the results of the hypothesis test using the Paired Sample T-Test showed a significance value of 0.000 which means less than 0.05 so that the results of the Paired Sample T-Test test stated that there was a significant difference between financial performance before and during the covid-19 pandemic in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2018-2021 period which stated that the H0 Hypothesis was accepted and the Ha Hypothesis was rejected.